Spectrophotometric Determination of Sulfacetamide and Sulfamethaxazole in Aqueous Solution Using Tetracyanoethylene Reagent - Omar A. Al-Taee (College of Education for Pure Sciences, 2012)
Abstract A simple and sensitive spectrophotometric method has been developed for determination of sulfacetamide and sulfamethaxazole. The method is based on the reaction of these drugs in aqueous solution with tetracyanoethylene reagent in the presence of sodium bicarbonate to produce yellow colored species measured at 355 and 356 nm for sulfacetamide and sulfamethaxazole respectively. Beer's law obeyed over the concentration range1-30 and 1-25 µg ml-1 with molar absorpitivity of 10575 and 13146 L.mol-1.cm-1 and sandell index of 0.0240 and 0.0192 μg.cm-2 for the above drugs respectively. It was found that these products were formed in ratio of 1:1. The method was applied successfully to the assay of sulfacetamide and sulfamethaxazole in their pharmaceutical formulations and was agreed well with the certified values and with standard addition procedure.